1998
DOI: 10.1051/agro:19980202
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of N deficiency in a wheat crop using physiological and radiometric methods

Abstract: -A winter wheat (cv Soissons) crop was made N deficient during stem elongation. The effects of the N stress were quantified by measuring the nitrogen nutrition index (NNI) (used as reference), proteolytic activity in the leaves, the rate of carbon dioxide (CO 2 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 27 publications
(29 reference statements)
1
30
0
1
Order By: Relevance
“…Therefore, we limited our analysis to the relationship between NNI and SPAD values of L4 at booting stage. The NNI was positively related to SPAD values (R In Europe, NNI is recognized as a reference method for detecting N deficiency in wheat crop (Justes et al, 1997;Vouillot et al, 1998). Because of the practical issues of using NNI are for crop diagnosis in farmers' fields, alternative methods are required to assess crop N status.…”
Section: Correlation Of Spad and Rspad Values With Nni Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we limited our analysis to the relationship between NNI and SPAD values of L4 at booting stage. The NNI was positively related to SPAD values (R In Europe, NNI is recognized as a reference method for detecting N deficiency in wheat crop (Justes et al, 1997;Vouillot et al, 1998). Because of the practical issues of using NNI are for crop diagnosis in farmers' fields, alternative methods are required to assess crop N status.…”
Section: Correlation Of Spad and Rspad Values With Nni Atmentioning
confidence: 99%
“…The non-linear relationship between SPAD values and NNI has been proved in fescue (Errecart et al, 2012), corn (Ziadi et al, 2008), wheat (Vouillot et al, 1998;Prost and Jeuffroy, 2007) and cocksfoot (Duru, 2002), and the correlation of RSPAD values with NNI, and relative grain yield has been studied only in corn (Ziadi et al, 2008) and wheat (Debaeke et al, 2006). Debaeke et al (2006) also found that the non-linear relationship between RSPAD values and NNI was not significantly affected by years, genotypes, and developmental stages.…”
mentioning
confidence: 99%
“…Optical techniques are not effective in estimating leaf N concentration directly; however, they are effective in estimating leaf chlorophyll concentration (Botha et al 2006). Leaf N and chlorophyll concentrations are frequently well correlated within an individual crop species, for example in wheat (Vouillot et al 1998), corn (Ercoli et al 1993) and potatoes (Vos and Bom 1993).…”
Section: Plant-based Diagnostic Testsmentioning
confidence: 99%
“…As a result, a reduced number of plants is usually sampled and the spatial heterogeneity of N needs is poorly represented. The estimation of the NNI based on spectral data has been proven feasible using field spectrometers operated on the ground [8] or mounted on tractors [9]. However the possibility to detect the N status using remotely rather than proximal sensed information has still to be tested [10].…”
Section: Introductionmentioning
confidence: 99%